2015
DOI: 10.1063/1.4915801
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the piezoelectric charge coefficient d33 of thick-film piezoelectric ceramics by varying poling and repoling conditions

Abstract: Piezoelectric ceramics are commonly used in various sensing applications. In this paper, the effect of poling and repoling conditions on thick-film piezoelectric ceramics were investigated. The piezoelectric charge coefficient of the piezoelectric ceramics were measured with varying poling conditions, where the effect of changing poling temperature and electrical field on the d 33 were analyzed. This was followed by investigating on the effect high applied electrical fields results in repolarization the alignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…There is one other well-known process to increase the piezoelectric constant of a polymer, namely, poling in a high external electrical field 35 [138][139][140]. It has also been reported that poling improves the piezoelectric properties of piezoceramics [141][142][143]. To facilitate poling and to collect the piezoelectric output voltage, electrodes must be applied.…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
See 1 more Smart Citation
“…There is one other well-known process to increase the piezoelectric constant of a polymer, namely, poling in a high external electrical field 35 [138][139][140]. It has also been reported that poling improves the piezoelectric properties of piezoceramics [141][142][143]. To facilitate poling and to collect the piezoelectric output voltage, electrodes must be applied.…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
“…Recently, E. Nilson et al reported that a strong piezoelectric effect can be achieved for PVDF fibres with a conductive composite based on carbon black and polyethylene using as high a poling voltage as possible and a poling temperature between 60 °C and 120 °C [144]. This can be explained by the heating of the polymer leading to an increase in the mobility of the molecular chain and, thus, a slight reduction in the coercive field and an increase in the charge- ceramics increased significantly as the poling electric field and poling temperature are increased [141][142][143].…”
Section: Additional Polarization and Other Ways To Improve Electroactmentioning
confidence: 99%
“…So, when compared with all the above inorganic piezoelectric materials, organic polymer materials have attracted much attention of researchers as they have various benefits such as chemical stability, lightweight, fabrication process, flexibility, non-toxicity, and biocompatibility. 14,34,129,130 Additionally, polymers have excellent mechanical properties and resistance to high temperatures with low dielectric constant, low density and low elastic stiffness, which results in high voltage sensitivity and makes them more suitable for sensor applications. 123,131,132 Table 3 indicates the property chart and applications of various organic and inorganic piezoelectric materials.…”
Section: Piezoelectric Characteristics Of Pvdfmentioning
confidence: 99%
“…Although this shows the direct biological effect of the nanomaterials, these effects are part of a highly complex biological system that is not yet fully understood and is difficult to compare to other systems with quantifiable piezoelectric coefficients, such as PVDF and ceramics. Moreover, precise studies in which the d 33 is varied (by changing poling time, field or temperature [356][357][358]) are necessary to study the impact of piezoelectric stimulation for a more rigorous understanding of the mechanism, as well as facilitating the design of optimum cell/tissue-specific systems for regeneration. This is best highlighted when discussing bone tissues, where the bone matrix is inherently piezoelectric [359] and piezoelectric stimulation is the mechanism that allows bone cells to adapt to changes in their environment [360].…”
Section: Piezoelectrics In Tissue Engineeringmentioning
confidence: 99%